Kemampuan Komunikasi Matematis Bermuatan Etnomatematika Melalui Model PBL Berbantuan Geogebra Ditinjau Dari Minat Belajar - Nurariva Siregar; Scolastika Mariani; Mohammad Asikin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to analyze students' mathematical communication skills in terms of interest in learning for fourth grade students with GeoGebra-assisted ethnomathematical learning. This research is a mixed methods research with a sequential explanatory design. The results showed that learning with Problem Based Learning containing ethnomathematics based on local culture assisted by GeoGebra on students' mathematical communication skills in terms of high learning interest showed good results from all indicators. Students' mathematical communication skills in terms of interest in learning are showing good results as well. Furthermore, students' mathematical communication skills in terms of low learning interest showed good results, this is because students have not been able to solve the problems that are in each indicator of mathematical communication skills. So that it can be concluded, PBL learning containing ethnomathematics assisted by GeoGebra fourth grade students of SDI Tamalanrea I Makassar is proven to be effective on the mathematical abilities of fourth grade students of SDI Tamalanrea I Makassar.